If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22y + 3 = 12y Reorder the terms: 3 + 22y = 12y Solving 3 + 22y = 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 3 + 22y + -12y = 12y + -12y Combine like terms: 22y + -12y = 10y 3 + 10y = 12y + -12y Combine like terms: 12y + -12y = 0 3 + 10y = 0 Add '-3' to each side of the equation. 3 + -3 + 10y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 10y = 0 + -3 10y = 0 + -3 Combine like terms: 0 + -3 = -3 10y = -3 Divide each side by '10'. y = -0.3 Simplifying y = -0.3
| x^8-7x^7-7x^6= | | 4(t-6)+8t=6(2t+5)-11 | | (3b^3-2b^2+b)(2b-3)= | | 5y^2-30y-135=0 | | 20c^2-17ct-63t^2=0 | | 3x+9=2(22-x) | | -u+3=2u+6 | | -11/9+1/2x-11/3x=3/2x-12/3-1 | | 15y-18y+1y=-2+40-2 | | 4(x-3)=x+15 | | 21/7+(-7/4)-32/5 | | 182/n=13 | | (y^2-5y+3)(2y^2+7y-4)= | | 6(1+3m)=-9(-2m+5)-4 | | 11n=143 | | (-2/3)+8=(4/3)+6 | | -313/18=-3/2+2/3x | | (r^2)-7r-18=0 | | (-2/3x1)+8=(4/3x1)+6 | | 84/12=n | | 317/18=-1/2-5/3n | | -16=x+6 | | -7y-33=4y | | -53/12-8/12 | | 0.35/4.9x7=X | | 3(x+6)=x+2 | | -52/12-8/12 | | 4/7y+2/-8=-7 | | -4=3y-1+14 | | x^2+2x+(-3)=0 | | (2x-4)(2x+5)= | | 9.6=x/6 |